Nondestructive Testing of CubSat Satellite Body Using Laser Vibrometry; Russian Journal of Nondestructive Testing; Vol. 55, iss. 5 - Derusova D. A. Dariya Aleksandrovna; Vavilov V. P. Vladimir Platonovich; Druzhinin N. V.; Kazakova O. I.; Nekhoroshev V. O.; Fedorov V. V. Vladislav Viktorovich; Tarasov S. Yu. Sergei Yulievich; Shpilnoy V. Yu. Viktor Yurjevich; Kolubaev Е. А. Evgeny Aleksandrovich (2019, 2019)
Title screen